Peran Kesadaran Hukum Literasi Digital Dalam Meningkatkan Ketahanan Siswa SMP Terhadap Hoax Dan Cyberbullying - Ira Kurniawan; Nugraha Gading Priandana; Lanang Maulana; Malikah Alya Azzahra; Perina Dwi Astuti; Ayu Nur Safitri; Luluk Maghfiroh; Rhaina Rifka Nefindia; Intan Rasita; Mila Agustin; Nadiyah Salamah; Karyadi Hidayat (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2026)
Abstract The rapid development of digital technology has significantly transformed students' lives, particularly in accessing information, communicating, and supporting learning activities. Alongside its benefits, digital advancement has also introduced various challenges, including the widespread dissemination of hoaxes and the increasing prevalence of cyberbullying among adolescents. These phenomena can negatively affect students’ psychological well-being, social interactions, and academic development. This article aims to examine the role of legal awareness and digital literacy in strengthening junior high school students' resilience against hoaxes and cyberbullying. The study employed a library research method with a descriptive qualitative approach by analyzing relevant scientific literature, previous research findings, and legal regulations. The findings indicate that legal awareness contributes to the development of responsible digital behavior through an understanding of rights, obligations, and the legal consequences of online activities. Meanwhile, digital literacy enhances students’ critical thinking skills, information verification abilities, understanding of digital ethics, and capacity to engage in healthy interactions within digital environments. The synergy between legal awareness and digital literacy plays a crucial role in improving students’ resilience in facing various digital risks. Therefore, collaboration among schools, families, government institutions, and society is essential in implementing sustainable legal education and digital literacy programs to foster a safe, healthy, and productive digital environment for students.